Integrated multiple hazard assessment associated with the road infrastructure environment. Application to roads in the province of Malaga (Spain). - Sortino-Barrionuevo, Juan Francisco; Reyes-Corredera, Sergio Jesús; Pardo García, Santiago Manuel; De-la-Fuente-Roselló, Ana Luisa (CNIG, 2020)
The study of risks near roads has been mainly addressed in the literature from a sectorial perspective, analysing independent processes linked to danger generation. In this work, infrastructure and its environment are considered an unique space of risk, proposing an integrated method which contemplates the simultaneous interaction in space of several kinds of threats which generally appear together in case of torrential rains: mass movements, dislocations of the road by substrate subsidence, artificial blocking of drainage systems due to solids moved by water erosion, flooding over the infrastructure in case of heavy rains, and flooding by overflowing of adjacent riverbeds. The proposed methods have been developed using a statistical approach, and the have been applied to several study areas in Southern Spain. We have implemented a semiautomatic GIS application, and the results show promising efficacy of the developed algorithm in order to predict critical points in roads.
https://cpage.mpr.gob.es/aviso-legal/
Keywords: Gestión de emergencias; Carreteras - Gestión; Multiple danger; Road Infrastructure; Mass Movements; Floods; Risk management